Customer innovation : customer-centric strategy for enduring growth - Debruyne, Marion (Kogan Page, 2014)
"A new set of organisations have discovered a new formula. They combine customer centricity with innovative power. These organisations have created a completely outside-in approach to the market. They are not driven by what they're good at. They start with the market and design their strategy around it. They replace practices of the past with a new set of capabilities, which enable them to be ahead of the curve in discovering new market opportunities. This enable them to develop new products and services faster than ever before and they hit the bull's eye in the market. Whereas the traditional value chain model regards the market as the end-outcome of the efforts of the organisation, the reversed value chain model starts there. The customer is the starting point and the value chain is the result of understanding customer needs and requirements. Packed with real world examples from a range of leading global companies including Disney, Coca-Cola, LEGO, Eurex, Netflix, KLM, Carglass, Komatsu, Callebaut and more, Marion Debruyne's provides every business with the framework it needs to combine customer focus with innovation to achieve success"--Resumé vydavatele